Determinants of Sports Injury in Young Female Swedish Competitive Figure Skaters - Jederström, Moa; Agnafors, Sara; Ekegren, Christina; Fagher, Kristina; Gauffin, Håkan; Korhonen, Laura; Park, Jennifer; Spreco, Armin; Timpka, Toomas (Frontiers in Sports and Active Living, 2021)
Introduction: Although figure skating attracts several hundred thousand participants worldwide, there is little knowledge about physical health and sports injuries among young skaters. The present study aimed to describe the health status of a geographically defined Swedish population of licensed competitive figure skaters and to examine injury determinants. Methods: All licensed competitive skaters in the southeastern region of Sweden were in April 2019 invited to participate in a cross-sectional study using an online questionnaire. Multiple binary logistic regression was used for the examination of injury determinants. The primary outcome measure was the one-year prevalence of a severe sports injury episode (time loss >21 days). The secondary outcome measure was the point prevalence of an ongoing injury. The determinants analyzed were age, skating level, relative energy deficiency indicators, and training habits. Results: In total, 142 (36%) skaters participated, 137 (96%) girls (mean (SD) age: 12.9 (SD 3.0) years). Participating boys (n=5) were excluded from further analysis. The one-year prevalence of a severe sports injury episode was 31%. The most common injury locations for these injuries were the knee (25%), ankle (20%) and hip/groin (15%). In the multiple model, having sustained a severe injury episode was associated with older age (OR 1.2, 95% CI 1.1-1.4; p=0.002) and an increased number of skipped meals per week (OR 1.1, 95% CI 1.0-1.3; p=0.014). The point prevalence of an ongoing injury episode was 19%. The most common locations were the knee (24%), ankle (24%) and foot (24%). Having an ongoing injury episode was associated with older age (OR 1.4, 95% CI 1.2-1.7; p<0.001) and an increased number of skipped meals per week (OR 1.1, 95% CI 1.0-1.3; p=0.049). Conclusion: One-third of young female Swedish competitive figure skaters had sustained a severe injury episode during the past year, and a fifth reported an ongoing episode. Older age and an increased number of skipped meals per week were associated with a sports injury episode. Long-term monotonous physical loads with increasing intensity and insufficient energy intake appear to predispose for injury in young female figure skaters. Further examination of injury determinants among competitive figure skaters is highly warranted.